Recruitment of skilled workers in companies that do not provide initial vocational training and measures to encourage more of them to do so - Wenzelmann, Felix [Verfasser]; Schönfeld, Gudrun [Verfasser] (My University, 2011)
"Most companies in Germany do not provide incompany vocational training for young people. What are their reasons for this, how do these companies meet their skilled labour needs, and what can be done to increase the share of companies that provide in-company vocational training? These questions are the focus of BIBB’s Company Survey on the Recruitment of Skilled Workers." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; Ausbildungsverhalten; Nachwuchssicherung; Betriebsbefragung